Expatriate support and success: A systematic review of organization-based sources of social support. Issue 4 (12th December 2016) - van der Laken, Paul; van Engen, Marloes; van Veldhoven, Marc; Paauwe, Jaap
Abstract : Purpose: The purpose of this paper is to review empirical research on the relationship between organization-based social support and the success of international assignments (IAs). Design/methodology/approach: Four search engines were used to obtain empirical studies relating organization-based social support to success criteria. Studies were compared based on type of theoretical foundation, criteria of success, source of social support and study design. Findings: The reviewed studies draw on three theoretical paradigms – based on stress, social capital and relational exchange. The results demonstrate that expatriates receive social support from multiple organization-based sources and that these sources' proximity to the expatriate influences the relationship between social support and success. Regarding geographical proximity, sources in the home and host countries fulfil different supportive functions and therefore stimulate different success criteria. Additionally, the success criteria stimulated by organizational support depend on the type of supportive practices offered. The impact of support from organizational members is further influenced by their hierarchical proximity to the expatriate, with supervisory support relating most strongly to success. In addition to proximity, characteristics of the expatriating employee and the assignment (e.g. expatriate motivation and assignment hardship) influence the value of social support. Finally, social support relates most strongly to expatriates' satisfaction, commitment, and adjustment and these frequently mediate its effect on expatriates' retention and performance. Research limitations/implications: Although only organization-based sources were considered, this review demonstrates that a multidimensional perspective is warranted when examining the effects of social support during IAs. Practical implications: This review provides insights into the ways organizations could and should assist (self-initiated) expatriates when aiming for specific outcomes. Originality/value: This in-depth examination of social support in the work environment of expatriates combines several theoretical paradigms and investigates multiple criteria of success.